Development of a biaxial grid-coil-type electromagnetic acoustic transducer. (25th November 2020) - Yang, Li-Jian; Zhang, Jia; Xing, Yan-Hao; Gao, Song-Wei; Xie, Zhe; Fu, Hong-Wen
Abstract: This study proposes a grid-coil-type transducer to achieve the simultaneous detection of axial and circumferential cracks in the pipeline, reduce the number of permanent magnets in dynamic detection, and improve crack detection efficiency. The proposed system can detect biaxial cracks in the pipeline. Based on Biot–Savart's Law, a mathematical model is established between the magnetic induction intensity and the coil of the electromagnetic acoustic transducer to determine the influence on the conductor. Experiments verify the relationship between the guided wave propagation characteristics of the grid-coil-type electromagnetic acoustic transducer and the ability to detect biaxial cracks. Results show that the grid-coil-type electromagnetic acoustic transducer can generate the biaxial ultrasonic guided wave propagating along the axial and circumferential pipeline, in which cracks are thereby simultaneously detected. Thus, the grid-coil-type electromagnetic acoustic transducer increases the detection scope, reduces the number of permanent magnets in dynamic detection, and improves crack detection efficiency. This study provides a theoretical and experimental basis for the research and engineering application of biaxial crack detection in the pipeline.